2016
DOI: 10.1002/acr.22824
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Patient‐Preferred Health and Treatment Outcomes in Early Rheumatoid Arthritis: A Longitudinal Qualitative Study

Abstract: From a patient perspective, normality is the ultimate outcome to target in ERA. Our study produced knowledge for designing more targeted therapeutic interventions aimed at normalizing patients' health and life in all its aspects during a crucial phase of RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 41 publications
5
45
1
Order By: Relevance
“…However, we showed a lower cumulative disease activity and faster treatment response on MTX with GCs over the first year, which seems more in accordance with patients' preferences 32. Moreover, the comparable safety profile in both low-risk arms provides important new evidence that GC remission induction is relatively safe in patients with so-called mild ERA.…”
Section: Discussionsupporting
confidence: 79%
“…However, we showed a lower cumulative disease activity and faster treatment response on MTX with GCs over the first year, which seems more in accordance with patients' preferences 32. Moreover, the comparable safety profile in both low-risk arms provides important new evidence that GC remission induction is relatively safe in patients with so-called mild ERA.…”
Section: Discussionsupporting
confidence: 79%
“…In a qualitative study evaluating early RA patients’ preferred health and treatment outcomes, van der Elst et al [44] confirmed the importance of attaining ‘normality’. Patients interviewed twice over 1 year after initiating treatment emphasized the importance of returning to normal in terms of disease control, improved pain and physical function, mental well being, and participation at work, home, and leisure.…”
Section: Additional Recent Publications Incorporating the Patient Permentioning
confidence: 99%
“…A whole treatment movement has grown out of this approach – “Treat To Target” – in which treatment is increased until patients achieve the defined target 7 . The growing focus on early treatment of inflammatory arthritis has been associated with an increased emphasis by patients on being able to return to normality as soon as possible 8 .…”
Section: Present Uncertaintiesmentioning
confidence: 99%